The Paediatric Wrist; Normal Age Related appearances on Magnetic Resonance Imaging and Radiographs. Follow up of a Healthy Cohort - Avenarius, Derk (UiT The Arctic University of Norway, 2017)
The papers of this thesis are not available in Munin. Paper I: Müller, L. S., Avenarius, D., Damasio, B., Eldevik, O. P., Malattia, C., Lambot-Juhan, K., Tanturri, L., Owens, C. M., Rosendahl, K.: “The paediatric wrist revisited: redefining MR findings in healthy children”. Available in Ann Rheum Dis. 2011, 70(4):605-10. Paper II: Avenarius, D. F., Ording Müller, L. S., Eldevik, P., Owens, C. M., Rosendahl, K.: “The paediatric wrist revisited - findings of bony depressions in healthy children on radiographs compared to MRI”. Available in Pediatr Radiol. 2012, 42(7):791-8. Paper III: Avenarius, D. F., Ording Müller, L. S., Rosendahl, K.: “Erosion or normal variant? 4-year MRI follow-up of the wrists in healthy children”. Available in Pediatr Radiol. 2016, 46(3):322-30. Paper IV: Avenarius, D. F., Ording Müller, L. S., Rosendahl, K.: “Joint fluid, bone marrow oedema like changes and ganglion cysts in the paediatric wrist; features that may mimic pathology. Follow-up of a healthy cohort”. Available in AJR Am J Roentgenol. 2017, 23:1-6. A cohort of 89 healthy children was recruited from Tromsø during 2009. All children had a radiograph and an MRI of the left wrist, while 74 met for a follow-up study during 2013. The initial examination showed that all children had numerous bony depressions in one or more of the carpal bones, and that these depressions could mimic erosions as defined in the adult rheumatoid arthritis literature, and other diseases seen in children. Moreover, around half of the children had at least one joint with more than 2 mm joint fluid, as well as bone marrow oedema-like changes in at least one of the carpal bones. In the 4-year follow-up we added a cartilage-specific MR-sequence to better characterize bony depressions. The results of the follow-up resembled those found during 2009, namely that the number of bony depression increased with age, that around one third had bone marrow oedema like changes in at least one of the carpal bones, and that half had joint fluid pockets deeper than 2 mm. ...